2011
DOI: 10.1007/s13148-011-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms in virus-induced tumorigenesis

Abstract: About 15–20% of human cancers worldwide have viral etiology. Emerging data clearly indicate that several human DNA and RNA viruses, such as human papillomavirus, Epstein–Barr virus, Kaposi’s sarcoma-associated herpesvirus, hepatitis B virus, hepatitis C virus, and human T-cell lymphotropic virus, contribute to cancer development. Human tumor-associated viruses have evolved multiple molecular mechanisms to disrupt specific cellular pathways to facilitate aberrant replication. Although oncogenic viruses belong t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 158 publications
(236 reference statements)
0
46
0
Order By: Relevance
“…It also is tempting to speculate that p12, and p12-like proteins of other carlaviruses, may be considered as a latency factor (a latent protein) of this group of viruses and the viral-programmed induction of hyperplasia might be a way to delay the onset of HR (a type of programmed cell death) and to maintain the latent state of the virus infection (e.g., cell division without virus replication), as it has recently been shown that overexpression of Nt E2FB1 reduces programmed cell death induction in tobacco Bright Yellow-2 cells (Smetana et al, 2012). Moreover, it has been well documented that in animal/human viruses, some latent stages induce tumorogenesis (Poreba et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…It also is tempting to speculate that p12, and p12-like proteins of other carlaviruses, may be considered as a latency factor (a latent protein) of this group of viruses and the viral-programmed induction of hyperplasia might be a way to delay the onset of HR (a type of programmed cell death) and to maintain the latent state of the virus infection (e.g., cell division without virus replication), as it has recently been shown that overexpression of Nt E2FB1 reduces programmed cell death induction in tobacco Bright Yellow-2 cells (Smetana et al, 2012). Moreover, it has been well documented that in animal/human viruses, some latent stages induce tumorogenesis (Poreba et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The oncogenic potential of DNA viruses is variable, and their role in cancer pathogenesis is mediated through various mechanisms, including, for example, mutagenic integration into the host genome and expression of oncogenic viral proteins (2,3). The elucidation of such mechanisms has played a key role in enhancing our understanding of cancer pathogenesis even as novel aspects of DNA virus biology continue to be unraveled (4).…”
mentioning
confidence: 99%
“…It has been found that genes encoded by oncogenic viruses such as HPV, Epstein-Barr virus, SV40, hepatitis B virus, and many others synthesize proteins which can interact with host epigenetic machinery leading to its deregulation. Studies have revealed that viral oncoproteins can indeed target the host genes such as DNMT, p53, pRB, and others, thereby altering the normal epigenetic mechanisms and acting as risk factors in the development and progression of cervical cancer [89][90][91] .…”
Section: Hpv and Other Pathogenic Infections Epigenetics And Cervicmentioning
confidence: 99%